Biosynthesis of ambrein in ambergris: evidence from isotopic data and identification of possible intermediates. Issue 8 (3rd April 2021) - Rowland, Steven J.; Sutton, Paul A.; Wolff, George A.
Abstract: Ambrein is found in ambergris, a coprolith occurring in the rectum of the sperm whale. In vitro, ambrein is produced by enzymatic cyclisation of squalene, via a monocyclic intermediate. However, little is known of the in vivo process. In order to find evidence for the reaction in vivo, a comparison was made of the δ 13 C relative isotopic ratios of ambrein in ambergris with those of co-occurring sterols. A statistically significant difference was noted. This suggests that ambrein originates via a different biosynthetic mechanism from that of the sterols. Examination of the minor constituents of a hydrogenolysed extract of ambergris revealed compounds with a bicyclic polypodane nucleus, rather than those with monocyclic structures. It is hypothesised that in vivo biosynthesis of ambrein proceeds, at least in some cases, via bacterial production of bicyclic polypodenols. The latter are known products of non-concerted squalene (or squalene oxide) cyclisations in other organisms. Graphical Abstract: